2017
DOI: 10.1016/j.jnutbio.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid regulates brown adipose tissue metabolism in high-fat-fed mice and in clonal brown adipocytes

Abstract: Brown adipose tissue (BAT) plays a key role in energy expenditure through its specialized thermogenic function. Therefore, BAT activation may help prevent and/or treat obesity. Interestingly, subcutaneous white adipose tissue (WAT) also has the ability to differentiate into brown-like adipocytes and may potentially contribute to increased thermogenesis. We have previously reported that eicosapentaenoic acid (EPA) reduces high-fat (HF)-diet-induced obesity and insulin resistance in mice. Whether BAT mediates so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 55 publications
8
90
3
2
Order By: Relevance
“…The preventative studies with pure EPA ethyl esters challenge some previous findings in this area of study. Earlies studies have reported a reduction in fat mass with EPA-enriched oils, which we did not observe 43,44 . Perhaps the differences in results lies in the concentration and purity of EPA and the timing as well as duration of intervention.…”
Section: Discussioncontrasting
confidence: 83%
“…The preventative studies with pure EPA ethyl esters challenge some previous findings in this area of study. Earlies studies have reported a reduction in fat mass with EPA-enriched oils, which we did not observe 43,44 . Perhaps the differences in results lies in the concentration and purity of EPA and the timing as well as duration of intervention.…”
Section: Discussioncontrasting
confidence: 83%
“…In the previous report [11], we investigated the effects of both EPA and DHA on cultured brown adipocytes. We observed more mitochondrial content with EPA than DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Ppar-α is highly expressed in BAT and increases levels of thermogenic marker including Pgc1α and Ucp1 [46], all of which are suitable targets for BAT activation and metabolic disorders. Moreover, some studies have already reported that n-3 PUFAs induce thermogenesis in BAT by increasing the level of Ppar-α and Pparγ [4749]. Beside the activation of BAT, omega 3 fatty acids act as natural ligands and activators of Ppar-α , which blocks NF-KB activity in WAT to prevent inflammation [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it also has been shown that v3 PUFAs favored the formation of the so-called "healthy adipocytes" with high number of mitochondria but not expressing UCP1 (Kuda et al, 2018). Moreover, other studies have shown the beneficial effect of v3 PUFA supplementation on glucose metabolism (glucose tolerance, insulin sensitivity) and on BAT activation and/or brite adipocyte formation (Kim and Goto, 2015;Pahlavani et al, 2017). In vivo studies have shown a global increase in thermogenesis in mice fed fish oil v3-enriched food, i.e.…”
Section: Pufas and Non-shivering Thermogenesismentioning
confidence: 99%